Influencia de las enmiendas orgánicas en el crecimiento y desarrollo de Solanum lycopersicum: datos de Baglung, Nepal - Kandel, Pradeep (2025)
An experiment was carried out in Baglung, Nepal, to determine how different soil amendments affected the growth and health of Srijana cv. tomato seedlings. The experiment followed a completely randomized design, with six treatments and four replications. The substrates were prepared using a variety of organic amendments, including control, cattle manure, goat manure, urea, vermicompost, and a coco peat-cattle manure blend. Soil amendments were applied in specific ratios that represented local farming practices. Observations included parameters such as germination percentage, emergence duration, leaf count, final plant stand, plant height, root length, root to shoot ratio, stem diameter, seedling vigor, and fresh/dry seedling weight. The findings revealed significant differences in seedling quality and performance due to various substrates. Seedlings grown in coco peat combined with cow dung had the highest germination percentage (75 %), required the fewest days (8) to reach 50 % germination, produced most leaves (27.5), had the tallest seedling height (26.55 cm), and had the highest final plant stand when compared to other treatments, followed by vermicompost. However, urea-treated seedlings displayed superior biomass accumulation. Control treatment showed inferior performance across most parameters except for a relatively higher root to shoot ratio (0.41). This study emphasizes the importance of soil amendment composition in influencing the early–stage growth and vigor of tomato seedlings, with specific treatments providing varying benefits across several growth metrics.